Interannual changes in winter-spring zooplankton estuarine community forced by hydroclimatic variability - With special reference to bioindicator species Eurytemora americana - Berasategui, Anabela Anhi (2023)
Climatic variability and anthropogenic pressures impact the structure and dynamics of pelagic ecosystems and copepods are good indicators of such changes. This investigation aims to explore the interannual pattern of the mesozooplankton community, in relation to environmental variables in the Bahía Blanca Estuary during winter-spring from last two decades focusing on the dominant species Eurytemora americana. Main changes recorded include increased temperature, alteration of the nutrient balance, a decrease in chlorophyll-a, modifications in the abundance-structure of the phytoplankton assemblages, and changes in the abundance-structure of the mesozooplankton community. A significant decrease was observed in species richness of the mesozooplankton over time. Alterations in abundance and reproductive traits of E. americana, were also found. The population of E. americana dropped from mean relative abundance of 47% in first years to 20-12% in lasts one, accompanied with an increase of copepod species characterized by higher trophic plasticity in eutrophic conditions, like Acartia tonsa and Euterpina acutifrons.